Association between red blood cell distribution width-to-albumin ratio and prognosis in post-cardiac arrest patients: data from the MIMIC-IV database - Cai, Yinhe; Zhang, Yao; Zhou, Ningzhi; Tang, Yong; Zheng, Haixia; Liu, Hong; Liang, Jiahua; Zeng, Ruixiang; Song, Shengqing; Xia, Yu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiac arrest (CA) triggers a systemic inflammatory response, resulting in brain and cardiovascular dysfunction. The red blood cell distribution width (RDW)-to-albumin ratio (RAR) has been widely explored in various inflammation-related diseases. However, the predictive value of RAR for the prognosis of CA remains unclear. We aimed to explore the correlation between the RAR index and the 30- and 180-day mortality risks in post-CA patients.MethodsClinical data were extracted from the MIMIC-IV database. The enrolled patients were divided into three tertiles based on their RAR levels (<3.7, 3.7–4.5, >4.5). Restricted cubic spline, Kaplan–Meier (K-M) survival curves, and Cox proportional hazards regression model were used to explicate the relationship between the RAR index and all-cause mortality risk. Subgroup analyses were also conducted to increase stability and reliability. The receiver operator characteristic (ROC) analysis was used to assess the predictive ability of the RAR index, red blood cell distribution width, and serum albumin for 180-day all-cause mortality.ResultsA total of 612 patients were eligible, including 390 men, with a mean age of 64.1 years. A non-linear relationship was observed between the RAR index and 180-day all-cause mortality, with a hazards ratio (HR) >1 when the RAR level exceeded 4.54. The K-M survival curve preliminarily indicated that patients in higher tertiles (T2 and T3) of the RAR index presented lower 30- and 180-day survival rates. An elevated RAR index was significantly associated with an increased 30-day [adjusted HR: 1.08, 95% confidence interval (CI): 1.01–1.15] and 180-day (adjusted HR: 1.09, 95% CI: 1.03–1.16) mortality risk. According to the ROC curve analysis, the RAR index outperformed the RDW and albumin in predicting all-cause 180-day mortality [0.6404 (0.5958–0.6850) vs. 0.6226 (0.5774–0.6679) vs. 0.3841 (0.3390–0.4291)]. The prognostic value of the RAR index for 180-day mortality was consistent across subgroups, and a significant interaction was observed in patients who were white, those with chronic pulmonary disease, or those without cerebrovascular disease.ConclusionThe RAR index is an independent risk factor for 30- and 180-day all-cause mortality in post-CA patients. The higher the RAR index, the higher the mortality. An elevated RAR index may be positively associated with adverse prognosis in post-CA patients, which can remind clinicians to quickly assess these patients.